INTEGRATION OF TRADITIONAL CHINESE MEDICINE INTO MODERN PHYSICAL THERAPY - Mihuță Andreea; Cojocariu Adrian (Sport şi Societate)
Movement therapy is known today as physical therapy and originates in Asia, with roots in religion and traditional medicine. The Tao-Tse people of ancient China record the earliest cases of therapeutic movement with the name "Cong Fu" in 3000 B.C.Traditional Chinese Medicine -TCM is based on the holistic concept of harmony between man and nature and is based on the use of natural resources, both inside and outside the human body, helping in the process of recovery, restoration and balancing of its health.TCM provides a unique view of health and disease, addressing the physical, emotional and spiritual aspects of the individual in an integrated way. This millennial tradition continues to exert a significant influence on global medical practice.Therefore, this article aims to offer a new perspective in the recovery process, based on ancient principles and urging to harmoniously combine old techniques and therapies with modern ones, in order to obtain optimal results for patients.Integrating TCM into physical therapy programs can be beneficial to support recovery and promote balance atthe body, mental, and emotional levels. It also offers patients a wide range of therapeutic options, promotes self-knowledge and responsibility in taking care of their own health.